2011
DOI: 10.1682/jrrd.2010.09.0177
|View full text |Cite
|
Sign up to set email alerts
|

Electromyogram pattern recognition for control of powered upper-limb prostheses: State of the art and challenges for clinical use

Abstract: Abstract-Using electromyogram (EMG) signals to control upper-limb prostheses is an important clinical option, offering a person with amputation autonomy of control by contracting residual muscles. The dexterity with which one may control a prosthesis has progressed very little, especially when controlling multiple degrees of freedom. Using pattern recognition to discriminate multiple degrees of freedom has shown great promise in the research literature, but it has yet to transition to a clinically viable op ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
613
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 809 publications
(663 citation statements)
references
References 70 publications
(86 reference statements)
11
613
0
4
Order By: Relevance
“…Such a device could be used as input to pilot a real hand prosthesis [2], a virtual avatar [3] and for clinical/rehabilitative purposes [4] on healthy subjects, as well as on transradial upper-limb amputees, who currently utilize EMG-controlled devices to partially substitute missing arm functionalities. In order to improve the performances of the proposed setup and to explore new possibilities related to EMG classification problems, we evaluated two separate approaches to preprocess and classify EMG data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a device could be used as input to pilot a real hand prosthesis [2], a virtual avatar [3] and for clinical/rehabilitative purposes [4] on healthy subjects, as well as on transradial upper-limb amputees, who currently utilize EMG-controlled devices to partially substitute missing arm functionalities. In order to improve the performances of the proposed setup and to explore new possibilities related to EMG classification problems, we evaluated two separate approaches to preprocess and classify EMG data.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its noninvasiveness and ease in acquisition, sEMG signals can be exploited by many human-computer interaction (HCI) devices as input to control a prosthesis [2] or a virtual device [3], either for interactive or clinical/rehabilitative purposes [4,5]. The development of such HCI systems can address the needs of transradial amputees, who could greatly benefit from the resulting augmentation of stump functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been widely accepted because of its relative ease of implementation and high performance [11].…”
Section: Data Processing and Classifiermentioning
confidence: 99%
“…Pattern recognition algorithms have been widely investigated in terms of real-time implementation and performance [7,[10][11], and a pattern recognition-based control system has recently been commercially deployed [12]. Low classification errors, in the range of 2.2 to 11.3 percent, have been reported for varying numbers (6 to 10) of wrist and hand movements using EMG pattern recognition techniques, such as linear discriminant analysis (LDA), artificial neural networks, and support vector machines (SVMs) [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Solutions that have been explored include prosthetic sockets incorporating methods of suspension [17], incompressible fluid [18], and struts arranged longitudinally with respect to the residual limb [19], so as to allow small movements of the prosthetic socket without altering the position of the electrodes. Studies towards the improvement of signal recognition [20], have also demonstrated a substantial improvement in the acquisition of the signal. However, there is a significant increase in the number of surface electrodes, which increases the discomfort of the users, and the training time in which they learn how to operate their prostheses.…”
Section: Myoelectric Control Systemmentioning
confidence: 99%